2005
DOI: 10.1111/j.1365-294x.2005.02424.x
|View full text |Cite
|
Sign up to set email alerts
|

High specificity generally characterizes mycorrhizal association in rare lady's slipper orchids, genus Cypripedium

Abstract: Lady's slipper orchids (Cypripedium spp.) are rare terrestrial plants that grow throughout the temperate Northern Hemisphere. Like all orchids, they require mycorrhizal fungi for germination and seedling nutrition. The nutritional relationships of adult Cypripedium mycorrhizae are unclear; however, Cypripedium distribution may be limited by mycorrhizal specificity, whether this specificity occurs only during the seedling stage or carries on into adulthood. We attempted to identify the primary mycorrhizal symbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
157
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 182 publications
(169 citation statements)
references
References 104 publications
(116 reference statements)
10
157
2
Order By: Relevance
“…As ceratobasidioid fungi have been found as symbionts or putatively symbionts of several orchid species, such as C. damasonium [10], C. longifolia [28], Cypripedium spp. [39], Dactylorhiza majalis (Reichenbach) P.F. Hunt et Summerhayes, E. gigantea, E. helleborine (L.) Crantz, E. palustris (L.) Crantz and Platanthera chlorantha (Cust.)…”
Section: Discussionmentioning
confidence: 99%
“…As ceratobasidioid fungi have been found as symbionts or putatively symbionts of several orchid species, such as C. damasonium [10], C. longifolia [28], Cypripedium spp. [39], Dactylorhiza majalis (Reichenbach) P.F. Hunt et Summerhayes, E. gigantea, E. helleborine (L.) Crantz, E. palustris (L.) Crantz and Platanthera chlorantha (Cust.)…”
Section: Discussionmentioning
confidence: 99%
“…Sebacinoid ORMs were detected in Epipactis palustris in a wetland site not accompanied by ectomycorrhizal plants in Northeast Bavaria, Germany (Bidartondo et al 2004). Shefferson et al (2005) found that high specificity generally characterizes ORMs in Cypripedium species from North America and Estonia. Mycoendophytes of terrestrial Acianthus, Caladenia and Pterostylis of Southeast Queensland appeared to be specific for their hosts (Bougoure et al 2005).…”
Section: Mycobionts Of Adult Terrestrial Orchidsmentioning
confidence: 99%
“…Molecular studies have shown that most fungi involved in most fungi involved in ORM are basidiomycetes (Taylor et al 2002;Shefferson et al 2005;Girlanda et al 2006Girlanda et al , 2011Suárez et al 2006;Pecoraro et al 2012b; Dearnaley Fungal interactions 3 et al 2012), but some orchid species form symbioses with ascomycetes (Bidartondo et al 2004;Selosse et al 2004;Shefferson et al 2008).…”
Section: Genetic and Functional Fungal Diversity In Mycorrhizal Symbimentioning
confidence: 99%